2014
DOI: 10.1109/tfuzz.2013.2251638
|View full text |Cite
|
Sign up to set email alerts
|

Individual Decision Making Can Drive Epidemics: A Fuzzy Cognitive Map Study

Abstract: Existing studies on the propagation of infectious diseases have not sufficiently considered the uncertainties that are related to individual behavior and its influence on individual decision making to prevent infections, even though it is well known that changes in behavior can lead to variations in the macrodynamics of the spread of infectious diseases. These influencing factors can be categorized into emotion-related and cognition-related components. We present a fuzzy cognitive map (FCM) denotative model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…[53], Poletti et al [54] , He et al [55] , Springborn et al [56]Mei et al . [43], Karimi et al . [45], Barrett et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[53], Poletti et al [54] , He et al [55] , Springborn et al [56]Mei et al . [43], Karimi et al . [45], Barrett et al .…”
Section: Resultsmentioning
confidence: 99%
“…The largest category embodies 76 references managing information as a dynamic parameter [3,25,34,40,43,4750,53,55,60,61,6568,70,71,74,77,80,82,86,92,9496,99,100,102,104109,113,115117,119126,128131,133,134,137,148,149,153,157,161,165,166,168,171178,184186,188,189]. In this category, instead of a threshold, the information is a continuous input in the decision-making process of individuals.…”
Section: Resultsmentioning
confidence: 99%
“…FCMs are used in numerous fields such as in engineering, error detection and medicine [36,37]. In this regard, Mei et al has applied FCM to describe how factors such as people's emotions and cognition functions influence each other to create epidemic infection [38]. FCM was also used by the Mago et al research to develop the required knowledge-based structure used for recognizing the specific causes and the symptoms of meningitis disease in children.…”
Section: The Fuzzy Cognitive Map Techniquementioning
confidence: 99%
“…In 2014, Duan et al [41] studied the spreading velocity of any epidemic based on topology of weighted graph created. In 2014, Mei et al [42] studied the effect of individual behavior during any epidemic using fuzzy cognitive map study. They simulated their framework for H1N1 infection and found that infection can be controlled at low level based on decision making of individuals.…”
Section: Ict and Mathematical Models In H1n1 Epidemicmentioning
confidence: 99%